2000
DOI: 10.1097/00005768-200008000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Short-term overtraining: effects on performance, circulatory responses, and heart rate variability

Abstract: The reduced maximal performance indicates a state of fatigue/overreaching and peripheral factors are suggested to limit performance even though HRmax and La(max) both were reduced. The reduced submaximal heart rates are probably a result of increased plasma volume. HRV in this group didn't seem to be affected by short-term overtraining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
129
0
16

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(158 citation statements)
references
References 22 publications
13
129
0
16
Order By: Relevance
“…However, between-subject variability was high in this investigation. Finally, Hedelin et al (2000a) reported increased HRV and decreased resting heart rate in a single "overtrained" athlete when compared to baseline measures. In comparison to normally responding subjects examined during the same period, the "overtrained" subject exhibited an increase in high frequency and total power in the supine position during intensified training, which decreased after recovery.…”
Section: Physiologymentioning
confidence: 88%
“…However, between-subject variability was high in this investigation. Finally, Hedelin et al (2000a) reported increased HRV and decreased resting heart rate in a single "overtrained" athlete when compared to baseline measures. In comparison to normally responding subjects examined during the same period, the "overtrained" subject exhibited an increase in high frequency and total power in the supine position during intensified training, which decreased after recovery.…”
Section: Physiologymentioning
confidence: 88%
“…No entanto, no presente estudo, a VFC não foi alterada significativamente quando analisada no domínio do tempo e da frequência em nenhuma das mensurações realizadas ao longo de 21 dias de treinamento de uma pré-temporada. Estes resultados são semelhantes aos obtidos no estudo de Hedelin et al 22 com canoístas de elite, no qual os componentes espectrais da VFC como o HF, LH e a razão LF/HF não sofreram alterações significativas com o overreaching logo após seis dias de treinamento em campo. Uma correlação inversa entre a VFC (SDNN, RMSSD e HF) e o volume e a intensidade do exercício quantificado pelo TRIMP foi observada no estudo de Earnest et al 13 com ciclistas profissionais ao final de três semanas de competição na Volta da Espanha.…”
unclassified
“…Porém no estudo de Halson et al 12 com ciclistas, houve uma diminuição significativa da Hgb durante duas semanas de treinamento intenso. Isto também foi constatado por Hedelin et al 22 em seu estudo com canoístas, no qual foi observada uma redução significativa na Hgb após seis dias de treino, a qual foi atribuída a um aumento do volume plasmático, que é considerado uma alteração que ocorre em resposta ao exercício.…”
unclassified
“…Oxytocin has been shown to increase directly after endurance running [22] and seems to have primarily parasympathetic actions such as slowing down the heart rate in trained individuals [23,24] a phenomenon related to training and overtraining syndrome [44]. This study aimed to investigate if analysis of Oxytocin levels could be an additional marker training stress such as overtraining syndrome since Oxytocin has been shown to have effects on stress management [1].…”
Section: Discussionmentioning
confidence: 99%